Smart leadership in universities: strategies for achieving sustainable development: Anbar University as a model - Saad Ali Mahmood,; Ehsan Salem Misri, (Technium Business and Management, 2025)
Rapid technological development has become the prevailing feature in our current era, which has led to intense competition between the organization, which has led to major economic complications and challenges. In this research, we will work to discover what has influenced smart leadership in universities as strategies for achieving sustainable development. In order to achieve the research objectives, a questionnaire was distributed to a purposive sample consisting of (66) individuals from the leadership at Anbar University The data was analyzed using the Statistical Analysis Program (SPSS), and the research reached a number of conclusions, the most important of which was that the results of the statistical analysis showed a positive correlation between smart leadership in its dimensions and sustainable development. As for the most prominent recommendations, the statistical results showed a weakness in explaining the variation in demographic variables, as they do not explain the differences in sustainable development.